Disalignments between the Policy Communication Process and Policy Discourse of the Comprehensive "Three-Child" Policy in Sina Weibo (The Journal of Medicine, Humanity and Media, 2023)
The transformation of China's family planning policy from a "state-planned" approach to one emphasizing "reproductive autonomy" is highlighted by the adjustment of the comprehensive "Three-Child Policy." This study examines the discrepancies in the communication process between the social media communication discourse and actual policy discourse of the "Three-Child Policy" on Sina Weibo. Findings reveal contradictions and inconsistencies between the communication process of the policy and the values, issues, and target audience conveyed by the original policy discourse. This provides an explanation for the deviation between official and public opinions regarding childbirth policy. At the policy discourse construction level, the essence of the positive family planning policy discourse lies in the cessation of the "planned" characteristics and the disappearance of the childbirth policy scorecard. However, in the communication process of the "Three-Child Policy," there is a reaffirmation of the state's "planned" attribute and an emphasis on promoting childbirth discourse, conflicting with the discourse of reproductive autonomy and friendliness. Additionally, targeting the two child families and unmarried individuals as the main subjects in policy communication, which would lead to a lack of focus on the intended groups of the family planning policy. In the era of after three-child policies, it is necessary to change the foothold of policy communication discourse from encouraging fertility to emphasizing fertility autonomy and fertility friendliness. In terms of policy issues, it is crucial to construct gender and family issues as policy concerns, intervening with public policy discourse that guides reproductive autonomy to overcome the discourse inertia of restrictive family planning policy and reinterpret the essence of the "new family planning".
Keywords: policy discourse; policy communication; family planing; three-child policy